2012
DOI: 10.1073/pnas.1120501109
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of neurons expressing agouti-related protein, but not melanin concentrating hormone, in leptin-deficient mice restores metabolic functions and fertility

Abstract: Leptin-deficient (Lep ob/ob ) mice are obese, diabetic, and infertile. Ablation of neurons that make agouti-related protein (AgRP) in moderately obese adult Lep ob/ob mice caused severe anorexia. The mice stopped eating for 2 wk and then gradually recovered. Their body weight fell to within a normal range for WT mice, at which point food intake and glucose tolerance were restored to that of WT mice. Remarkably, both male and female Lep ob/ob mice became fertile. Ablation of neurons that express melanin-concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 43 publications
(42 reference statements)
4
81
0
Order By: Relevance
“…Deletion of PI3K signaling in LR cells caused lack of responsiveness of AgRP to metabolic cues, potentially leptin, resulting in higher AgRP expression in fed conditions, associated with increased food intake. The AgRP neurons have inhibitory actions on the reproductive axis (51)(52)(53). Therefore, high levels of AgRP may have disrupted the reproductive function of LR Δα mice.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of PI3K signaling in LR cells caused lack of responsiveness of AgRP to metabolic cues, potentially leptin, resulting in higher AgRP expression in fed conditions, associated with increased food intake. The AgRP neurons have inhibitory actions on the reproductive axis (51)(52)(53). Therefore, high levels of AgRP may have disrupted the reproductive function of LR Δα mice.…”
Section: Discussionmentioning
confidence: 99%
“…Further supporting the idea that insulin and/or leptin must restrain NPY/AgRP neurons to permit fertility, it was shown that ablating NPY/AgRP-expressing neurons in leptin-deficient (ob/ob) diabetic mice was able to restore their fertility, food intake regulation and glucose tolerance (Wu et al 2012). Additionally, AgRP deficiency alone (vs neuronal ablation) in LepR-null (db/db) mice was also able to rescue their HPG axis function (ShefferBabila et al 2013).…”
Section: Npy/agrp-expressing Neuronsmentioning
confidence: 86%
“…It is likely that the AgRP neurons and the GnRH neurons are either directly or indirectly connected (24) and that this circuitry dictates the reproductive phenotypes observed in several reports, including the one in PNAS (1). An intriguing question is how hypothalamic circuitry adapts to the lack of AgRP neurons reversing infertility in ob/ob mice in the complete absence of leptin.…”
Section: Agrp Neurons and Reproductionmentioning
confidence: 99%
“…The cellular mechanisms involved in the fine coordination of energy balance and reproduction are largely unknown. In PNAS, Wu et al (1) shed light on a previously unsuspected neuronal population that appears to be fundamental for the coupling of energy deficit with impaired reproduction.…”
mentioning
confidence: 99%